Live Coding Patterns and a Toolkit for Pure Data. - Brown, Andrew R. (Organised Sound, 2023)
Creative activities often involve specific processes and techniques that reflect the unique nature of the activity. For live coders, these processes and techniques can be expressed as algorithms and functions in live coding languages. In many fields, these idiomatic processes are referred to as design patterns. Design patterns are important to understand because they can structure thought and direct users towards particular outcomes. This article examines the design patterns in live coding practices and languages, specifically focusing on the Live Coding Toolkit for Pure Data. Pure Data is a visual programming language, but few live coders have traditionally used it. This article explains how the Live Coding Toolkit allows Pure Data to effectively express the patterns of practice required for successful music live coding performance.